1995
DOI: 10.1071/ea9950223
|View full text |Cite
|
Sign up to set email alerts
|

Conservation tillage increases in soil water storage, soil animal populations, grain yield, and response to fertiliser in the semi-arid subtropics

Abstract: We compared 4 tillage practices (traditional, stubble mulch, reduced, no tillage) during 10 years under rainfed conditions on an alluvial soil in the semi-arid subtropics of central Queensland. In the final 4 years, responses to applied fertiliser nitrogen (N), sulfur (S), and zinc (Zn) were determined. We measured soil water storage, soil nitrate accumulation, grain yield (sorghum, wheat), grain protein content, and populations of soil macrofauna, with the aim of identifying soil-conserving practices that als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 18 publications
2
37
1
1
Order By: Relevance
“…More detailed descriptions of the tillage trials at Warwick (Hermitage) and Biloela are available in Thomas et al (2003) and Radford et al (1995), respectively, while descriptions of the Tulloona fertiliser trial appear in Lester and Dowling (2001) and Lester et al (2003). The Toowoomba (Wellcamp) tillage trial site had been sown to annual crops of winter wheat, with similar combinations of stubble management and tillage as Hermitage, but had only run for 9 consecutive seasons at the time of sampling, compared with the 35 years of predominantly annual wheat cropping at Hermitage (Thomas et al 2003).…”
Section: Experimental Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…More detailed descriptions of the tillage trials at Warwick (Hermitage) and Biloela are available in Thomas et al (2003) and Radford et al (1995), respectively, while descriptions of the Tulloona fertiliser trial appear in Lester and Dowling (2001) and Lester et al (2003). The Toowoomba (Wellcamp) tillage trial site had been sown to annual crops of winter wheat, with similar combinations of stubble management and tillage as Hermitage, but had only run for 9 consecutive seasons at the time of sampling, compared with the 35 years of predominantly annual wheat cropping at Hermitage (Thomas et al 2003).…”
Section: Experimental Sitesmentioning
confidence: 99%
“…Duczek and Wildermuth 1991). Similarly, there has been extensive research to investigate the interactions between cropping systems and the beneficial impact of soil macrofauna (Radford et al 1995;Wilson-Rummenie et al 1999) and mycorrhizae, (Thompson 1987), but other beneficial components of the soil biota have received limited (Roper et al 1994) or no attention. In particular, there has been little concerted effort to explore the broader impact of crops and cropping systems on the constituents and relative activities of biota constituting the detritus food web, and the impact of any changes on subsequent crop productivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimal-and zero-tillage farming has been demonstrated to have both economic and soil conservation benefits in the subtropical cereal belt (Freebairn and Wockner 1986;Radford et al 1995).…”
Section: Tillage Practicesmentioning
confidence: 99%
“…Benjamin (1993) and Baumhart & Lescano (1996) indicated that soils under no-tillage treatment have greater infiltration rates and water storage capacities than tilled soils. Conservation tillage was also shown to improve soil water content and crop yields in many environments (Radford et al 1995;Hemmat & Eskandari 2004;Munoz et al 2007), but Wilhelm et al (1987) and Hammel (1995) observed negative effects of no-tillage on crop yields in arid areas of the United States.…”
Section: Introductionmentioning
confidence: 99%